Uganda : Third Review Under the Policy Support Instrument-Staff Report; and Press Release. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Uganda's Third Review Under the Policy Support Instrument (PSI). Supported by generally sound policies, Uganda's economic performance was positive in FY2013/14. All quantitative assessment criteria and structural benchmarks were met, and the authorities have taken action to address the shortfall in tax revenue collection. Progress toward the achievement of other key structural reforms has proceeded as expected. The envisaged policy mix is set to maintain the growth momentum in FY2014/15. Based on the satisfactory program performance and the proposed policies, IMF staff supports completion of the third PSI review.